2017
DOI: 10.3847/1538-4357/aa7746
|View full text |Cite
|
Sign up to set email alerts
|

Orbit Alignment in Triple Stars

Abstract: Statistics of the angle Φ between orbital angular momenta in hierarchical triple systems with known inner visual or astrometric orbits are studied. Correlation between apparent revolution directions proves partial orbit alignment known from earlier works. The alignment is strong in triples with outer projected separation less than ∼50 AU, where the average Φ is about 20• . In contrast, outer orbits wider than 1000 AU are not aligned with the inner orbits. It is established that the orbit alignment decreases wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 22 publications
5
52
0
Order By: Relevance
“…Nevertheless, a trend of smaller inner eccentricities at projected outer separations s < 100 au is emerging. As noted by Tokovinin (2017), compact hierarchies also tend to have more aligned orbits. Further accumulation of data on orbits in hierarchical stellar systems, especially in compact ones, will help to clarify these trends.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Nevertheless, a trend of smaller inner eccentricities at projected outer separations s < 100 au is emerging. As noted by Tokovinin (2017), compact hierarchies also tend to have more aligned orbits. Further accumulation of data on orbits in hierarchical stellar systems, especially in compact ones, will help to clarify these trends.…”
Section: Discussionmentioning
confidence: 74%
“…Kepler-1647, Kostov et al 2016). Low-mass triple systems with outer separations of the order of ∼50 au or less also have a strong alignment trend, even though the typical relative angles between orbital planes are still substantial, ∼30 • (Tokovinin 2017). Formation of companions in a massive circumstellar disc, their subsequent growth and inward migration seem to match the prevalent architecture of compact "planetary-like" (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…This choice of orbital angles corresponds to isotropic orbital distributions. However, observations suggest that the orbital alignment in triple stars is not isotropic (Tokovinin 1993;Sterzik & Tokovinin 2002), and, in particular, is correlated with the separation of the tertiary companion (Tokovinin 2017). Tokovinin (2017) found that tight triples with inner semimajor axes less than about 50 tend to be aligned in their orbits (with a mean mutual inclination of Φ ∼ 20 • ), whereas triples with wider inner orbits tend to have isotropic relative orbital orientations.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…(below the opacity limit), actually have quasi-planar architectures (Borkovits et al 2016;Tokovinin 2017). Not only does this severely limit the fraction of triples that undergo Kozai-Lidov oscillations, but points to the dominant role of disk fragmentation and migration in the formation of close binaries and compact triples (see also Tobin et al 2016).…”
Section: Introductionmentioning
confidence: 98%